Study on an Axial Flow Hydraulic Turbine with Collection Device - Yasuyuki Nishi; Terumi Inagaki; Kaoru Okubo; Norio Kikuchi (International Journal of Rotating Machinery)
We propose a new type of portable hydraulic turbine that uses the kinetic energy of flow in open channels. The turbine comprises a runner with an appended collection device that includes a diffuser section in an attempt to improve the output by catching and accelerating the flow. With such turbines, the performance of the collection device, and a composite body comprising the runner and collection device were studied using numerical analysis. Among four stand-alone collection devices, the inlet velocity ratio was most improved by the collection device featuring an inlet nozzle and brim. The inlet velocity ratio of the composite body was significantly lower than that of the stand-alone collection device, owing to the resistance of the runner itself, the decreased diffuser pressure recovery coefficient, and the increased backpressure coefficient. However, at the maximum output tip speed ratio, the inlet velocity ratio and the loading coefficient were approximately 31% and 22% higher, respectively, for the composite body than for the isolated runner. In particular, the input power coefficient significantly increased (by approximately 2.76 times) owing to the increase in the inlet velocity ratio. Verification tests were also conducted in a real canal to establish the actual effectiveness of the turbine.